A highly efficient copper and ligand free protocol for the room temperature Sonogashira reaction. Issue 1 (1st December 2014) - Gogoi, Ankur; Dewan, Anindita; Bora, Utpal
Abstract : A mild and efficient catalytic system based on PdCl2 and Na2 SO4 has been developed for the Sonogashira reaction of aryl iodides at room temperature. Abstract : A mild and efficient catalytic system based on PdCl2 and Na2 SO4 has been developed for the Sonogashira reaction of aryl iodides at room temperature. The system provides a simple route to obtain polyfunctional alkynes under ligand and copper free conditions. The procedure is equally efficient for aliphatic alkynes and aryl bromides.